A revision of the genus Notodascillus Carter (Coleoptera: Dascillidae) - Jin, Zhenyu; Ślipiński, Adam; Pang, Hong (Zootaxa, 2013)
The Australian species of Notodascillus Carter are revised based on examination of available type material and extensive collections. Three very closely related species have been recognised: N. brevicornis (Macleay), N. sublineatus Carter and N. iviei sp. n. Detailed generic and species descriptions, key to the species and distribution data are provided.